O CONSUMO COLABORATIVO EM ESTRATOS ECONÔMICOS A E B NA CIDADE DE SÃO PAULO – SP - ORSI, DANIELLA FERNANDES DE OLIVEIRA (2017)
This study aimed to investigate the practices of collaborative consumption, in the social strata A and B of the city of São Paulo, by analyzing the facilities, difficulties and the real interests of the interviewees to increasingly seek access and sharing instead of Ownership of products and services. The research question considers how collaborative consumption can be expanded in order to establish a win - win system for businesses and consumers, as well as to understand if this practice is driven by social, economic or technological drivers (OWYANG, 2013c). It is presented as the collaborative consumption established in society, driven by the internet, creating a new culture, based on the consumption systems defined by Botsman and Rogers (2011) and in the twelve categories classified by Owyang et al. (2014). With the purpose of giving subsidies to the companies to develop more appropriate strategies next to this new profile of consumption, a qualitative, exploratory descriptive study was developed through a bibliographical review and semi-structured interviews in field research. The results indicate the real interests of respondents about the products or services made available on the collaborative consumption beyond the knowledge of which services are used, identifying the specifics of these social classes sharing phenomenon. It has also been possible to infer that the interest with respect to the practice of collaborative consumption is driven by several factors, one being the economic factor as the paramount among the respondents. To finalize the study are presented business and academic contributions and suggestions for research on the topic